2011
DOI: 10.1128/aem.05259-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chemical Chaperones in Improving the Solubility of Recombinant Proteins in Escherichia coli

Abstract: The recovery of active proteins from inclusion bodies usually involves chaotrope-induced denaturation, followed by refolding of the unfolded protein. The efficiency of renaturation is low, leading to reduced yield of the final product. In this work, we report that recombinant proteins can be overexpressed in the soluble form in the host expression system by incorporating compatible solutes during protein expression. Green fluorescent protein (GFP), which was otherwise expressed as inclusion bodies, could be ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 38 publications
1
44
0
1
Order By: Relevance
“…The same effect was also observed with glycine [Diamant et al, 2001[Diamant et al, , 2003]. In accordance with the experiments of Prasad et al [2011], osmolytes help in the solubilization of proteins if they can permeate the cell membrane and participate in ATP generation. In our case, betaine is not a compound metabolized by E. coli , but it has a positive effect on the solubility of IFN-α5.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The same effect was also observed with glycine [Diamant et al, 2001[Diamant et al, , 2003]. In accordance with the experiments of Prasad et al [2011], osmolytes help in the solubilization of proteins if they can permeate the cell membrane and participate in ATP generation. In our case, betaine is not a compound metabolized by E. coli , but it has a positive effect on the solubility of IFN-α5.…”
Section: Resultssupporting
confidence: 68%
“…Usually, the addition of osmolytes is combined with other methods such as osmotic and/or heat shock or plasmid-induced chaperone co-expression [Choi et al, 2010;De Marco et al, 2005;Oganesyan et al, 2007;Schultz et al, 2007]. In a recent paper, Prasad et al [2011] have attempted to understand the mechanism by which the osmolytes increase the solubility of heterologous protein. They found that the solubilization of green fluorescent protein in vivo was proportional to the concentration of ATP produced in the cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is well known that arginine and other metabolites such as trehalose and glycine betaine, among others, can enhance in vivo protein folding. 68, 69 The enhancement in solubility might also be due to simple differences in metabolism between E. coli using ethanolamine as an energy source and E. coli using glucose.…”
Section: Resultsmentioning
confidence: 99%
“…Sorbitol is known to improve production of soluble recombinant proteins in E. coli [33] and also increases solubility of intracellular FVIII aggregates, hence improves transport from endoplasmic reticulum to golgi in mouse models [34]. Sorbitol is also reported to be involved in initiation and facilitation of proper folding of several mutants of human cystathionine β-synthase [35].…”
Section: Introductionmentioning
confidence: 99%